Drug use in prisoners: epidemiology, implications, and policy responses - Kinner, Stuart A. (Oxford University Press, 2018)
"In most countries, problematic drug use is dealt with primarily as a criminal justice issue, rather than a health issue. Accordingly, a large proportion of people in prison have a history of alcohol, tobacco and/or illicit drug use and, despite the best efforts of correctional authorities, some continue to use these substances in prison, often in very risky ways. After release from prison, many relapse to risky substance use, and are at high risk of poor health outcomes, preventable death, or reincarceration.In this edited volume, for the first time we bring together 40 contributors from 10 countries to review what is known about alcohol, tobacco and illicit drug use in people who cycle through prisons, and the harms associated with use of these substances. We consider some evidence-based responses to these harms - both in prison and after return to the community - and discuss their implications for policy reform.This book is international in scope and multi-disciplinary in character. It brings together and integrates the perspectives of public health and addictions researchers, criminologists and correctional leaders, epidemiologists, physicians, and human rights lawyers. Our contributors are unified in their commitment to evidence-informed policy - that is, doing what we know works. An overarching theme pervading all of the chapters is that people who cycle through prisons come from the community, and almost always return to the community. Their health problems are therefore our health problems; in other words, 'prisoner health is public health'"--Provided by publisher